2015
DOI: 10.1111/ggi.12670
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gum chewing exercises on saliva secretion and occlusal force in community‐dwelling elderly individuals: A pilot study

Abstract: Aim: Elderly individuals face the risk of reductions in saliva secretion and occlusal force caused by systemic diseases or medications that can eventually result in malnutrition and systemic complications. We tested the hypothesis that regular gum chewing exercises (GCE) would enhance saliva secretion and occlusal force in an elderly population. Methods:A total of 12 community-dwelling elderly individuals (3 men and 9 women) participated in this study after providing informed consent. Participants carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 30 publications
1
40
0
Order By: Relevance
“…The gum chewing exercise has been used previously to improve bite force and masticatory function (Kiliaridis et al, 1995; Masumoto et al, 2009; Nakagawa et al, 2017; Ohira et al, 2012; van Bruggen et al, 2015). In this study, the mean MBF value of all subjects increased from 468 to 574 N after 4‐week chewing exercise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gum chewing exercise has been used previously to improve bite force and masticatory function (Kiliaridis et al, 1995; Masumoto et al, 2009; Nakagawa et al, 2017; Ohira et al, 2012; van Bruggen et al, 2015). In this study, the mean MBF value of all subjects increased from 468 to 574 N after 4‐week chewing exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, masticatory exercise seems important in improving masticatory disturbance and deficiency. It has been reported that gum chewing exercise is helpful in enhancing bite force and masticatory function (Kiliaridis, Tzakis, & Carlsson, 1995; Masumoto, Yamaguchi, & Fujimoto, 2009; Nakagawa et al, 2017; Ohira, Ono, Yano, & Takagi, 2012; van Bruggen et al, 2015). Kiliaridis et al (1995) reported that 4‐week training with hard chewing gum influenced the functional capacity of the masticatory muscles and increased their strength.…”
Section: Introductionmentioning
confidence: 99%
“…Thirteen full-text copies of the remaining studies were obtained and subjected to further evaluation. After reading full-text copies, seven studies were excluded from this systematic review due to the following reasons: (i) one studied was performed in adolescents' individuals [10]; (ii) four studies did not evaluate orofacial or cognitive functions [28][29][30][31]; (iii) one study [32] did not present a non-exercise control group or other intervention groups for comparison to the chewing intervention group; and (iv) one study performed an acute chewing intervention [33]. Therefore, at the end of the process, six publications meeting the eligibility criteria were included for qualitative analysis [34][35][36][37][38][39], of which five studies evaluated orofacial function [34][35][36][37][38], and one study evaluated cognitive function [39].…”
Section: Included Studiesmentioning
confidence: 99%
“…The protocol of the exercises was as follows: a gumchewing exercise with a soft gum was carried out for 2 weeks, followed by a 2-week rest period, and then a gum-chewing exercise with a hard gum for 2 weeks. This method contributes to the improvement of occlusal force, amount of saliva secretion, and mucosal moisture in older adults with natural bilateral posterior occlusion (Nakagawa et al 2017). Increasing food consistency for older adults with dementia not accompanied by dysphagia is also effective in improving chewing ability and QOL (Weijenberg et al 2013).…”
Section: Examples Of Interventionsmentioning
confidence: 99%